Myocardial perfusion reserve and strain-encoded CMR for evaluation of cardiac allograft microvasculopathy - Erbel, Christian; Gleißner, Christian A.; Hofmann, Nina; Akhavanpoor, Mohammadreza; Wangler, Susanne; Dösch, Andreas; Voß, Andreas; Buß, Sebastian Johannes; Schnabel, Philipp Albert; Katus, Hugo; Korosoglou, Grigorios (JACC Cardiovascular imaging, 2016)
Objectives: This study sought to evaluate myocardial perfusion reserve index (MPRI) and diastolic strain rate, both assessed by cardiac magnetic resonance (CMR) as a noninvasive tool for the detection of microvasculopathy.Background: Long-term survival of cardiac allograft recipients is limited primarily by cancer and cardiac allograft vasculopathy (CAV). Besides epicardial CAV, diagnosed by coronary angiography, stenotic microvasculopathy was found to be an additional independent risk factor for survival after heart transplantation. Methods: Sixty-three consecutive heart transplant recipients who underwent CMR, coronary angiography, and myocardial biopsy were enrolled. Stenotic vasculopathy in microvessels was considered in myocardial biopsies by immunohistochemistry and CAV was graded during coronary angiography according to International Society of Heart and Lung Transplantation criteria. In addition, by CMR microvasculopathy was assessed by myocardial perfusion reserve during pharmacologic hyperemia with adenosine and strain-encoded magnetic resonance using a modified spatial modulation of magnetization tagging pulse sequence in all patients. Results: Decreasing MPRI and diastolic strain rates were observed in patients with decreasing microvessel luminal radius to wall thickness ratio and decreasing capillary density (r = 0.45 and r = 0.61 for MPRI and r = 0.50 and r = 0.38 for diastolic strain rate, respectively; p < 0.005 for all). Using multivariable analysis, both MPRI and diastolic strain rate were robust predictors of stenotic microvasculopathy, independent of age, organ age, and CAV by International Society of Heart and Lung Transplantation criteria (hazard ratio: 0.07, p = 0.006 for MPRI; hazard ratio: 0.91, p = 0.002 for diastolic strain rate). Patients without stenotic microvasculopathy in the presence of no or mild CAV (n = 36) exhibited significantly higher median survival free of events, compared with patients with stenotic microvasculopathy in the presence of no or mild CAV (n = 18; p = 0.04 by log rank). Conclusions: CMR represents a valuable noninvasive diagnostic tool, which may be used for the early detection of transplant microvasculopathy before the manifestation of CAV during surveillance coronary angiographic procedures.
Gesehen am 30.11.2017